2004
DOI: 10.1007/s00134-003-2022-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of acute lung injury in European intensive care units

Abstract: Acute lung injury was frequent in our sample of European ICUs (7.1%); one third of patients presented with mild ALI, but more than half rapidly evolved to ARDS. While the mortality of ARDS remains high, that of mild ALI is twice as low, confirming the grading of severity between the two forms of the syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
282
12
22

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(340 citation statements)
references
References 41 publications
24
282
12
22
Order By: Relevance
“…The discrepancy of basic diseases between the ARDS and non‐ARDS group might limit the clinical application of this study. In addition, the mortality of ARDS group in this study seems to be higher than other reported studies 1, 2, 3. This is probably due to the heterogeneity of different study populations.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The discrepancy of basic diseases between the ARDS and non‐ARDS group might limit the clinical application of this study. In addition, the mortality of ARDS group in this study seems to be higher than other reported studies 1, 2, 3. This is probably due to the heterogeneity of different study populations.…”
Section: Discussioncontrasting
confidence: 60%
“…Acute respiratory distress syndrome (ARDS), characterized by permeability pulmonary edema and refractory hypoxemia, has an enormous effect on both morbidity and mortality 1, 2, 3. The Berlin definition is widely accepted for diagnosing ARDS, and the diagnosis is predominantly based on oxygenation index and chest X‐ray 4.…”
Section: Introductionmentioning
confidence: 99%
“…Because pulmonary inflammation precedes the onset of clinically defined ARDS, the identification of factors that can accelerate or augment inflammation in the pathogenesis of ARDS could lead to new therapeutic approaches to limit disease incidence and reduce mortality. Patients frequently develop ALI after admission to the hospital (2)(3)(4)(5), implying a possibility that potentially modifiable in-hospital exposures could contribute to the development of ALI in predisposed hosts. Supplemental oxygen (40-60%) comprises one such exposure (4)(5)(6).…”
mentioning
confidence: 99%
“…Although many therapeutic strategies have been developed clinically [1,2,3], the mortality and morbidity associated with acute respiratory distress syndrome (ARDS) remains very high [4]. Since acute lung injury is nonhomogenous [5], some lung areas are less affected and therefore more compliant.…”
Section: Introductionmentioning
confidence: 99%